2019
DOI: 10.1016/j.jcot.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic union score for tibia fractures predicts success with operative treatment of tibial nonunion

Abstract: Background: The purpose of this study is to evaluate the ability of preoperative and postoperative radiographic union scores for tibia fractures (RUST) to predict treatment success of tibia fracture nonunion. Materials and methods: Patients presenting for operative treatment of tibia fracture nonunion were enrolled in a prospective data registry. Enrolled patients were followed at regular intervals for 12 months. Preoperative and 12 week postoperative radiographs were reviewed and scored using the RUST criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…More recently, Christiano et al demonstrated the utility of the RUST score in patients with aseptic tibial nonunion undergoing reoperation to promote healing. Amongst 68 patients presenting, a RUST score of less than 7 predicted persistent non-union even after secondary surgery (sensitivity 1, specificity 0.75) [25]. Lastly, a recent review by our group identified that functional status was a reliable predictor of tibial union [26].…”
Section: Discussionmentioning
confidence: 94%
“…More recently, Christiano et al demonstrated the utility of the RUST score in patients with aseptic tibial nonunion undergoing reoperation to promote healing. Amongst 68 patients presenting, a RUST score of less than 7 predicted persistent non-union even after secondary surgery (sensitivity 1, specificity 0.75) [25]. Lastly, a recent review by our group identified that functional status was a reliable predictor of tibial union [26].…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, the radiological union was evaluated by RUST score. e RUST scoring system, with its advent way back in 2010, has shown a formidable performance with excellent intra-and interrater reliability for grading union and predicting union in tibial shaft fractures [18][19][20][21]. For clinical evaluation, we chose the LEFS score.…”
Section: Discussionmentioning
confidence: 99%
“…e primary outcome measures were to analyze the radiological union and the functional status of the limb. e radiological union scale in tibial fractures (RUST) score was used for the estimation of radiological union, and the lower extremity functional scale (LEFS) was used for the assessment of functional status [18][19][20][21][22][23]. e RUST scoring system (range � 4-12) utilises X-rays in both anteroposterior and lateral views to assess union by documenting the bridging callus and visible fracture line in all four cortices.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic union score (RUS) and modified RUS were developed to overcome the subjective nature of visual, radiographic evaluation, and clinical correlation in patients with delayed or non-union. 14 Studies showed good interobserver agreement in validation studies, even in complex bone defects and in patients with co-morbidities. These are not routinely used in clinical practice and still suffer from the fundamental limitation of being semiquantitative and subjective.…”
Section: Assessment Of Fracture Unionmentioning
confidence: 91%